(untitled) (Journal of Plant Disease Sciences, 2022)
Sweet orange (Citrus sinensis) are the second largest citrus fruit cultivated in the country. Several diseases are responsible for citrus decline in which dry root rot disease caused by Fusarium solani is more prevalent. During the survey mean dry root-rot incidence was highest (18.43 %) in Jalna district followed by Beed (14.26%) and lowest in Ahmednagar district (9.65%). Significant morphogenic variability was observed in nine isolates of Fusarium solani with respect to size, shape, septation, colour of micro conidia macro conidia and chlamydospores. Czapek’s Dox Agar media recorded maximum growth (84.04 mm) followed by Richard Agar media (82.48 mm) whereas; the least growth was observed on Rose Bengal Agar media (58.74 mm).